Stress, anxiety and depression scale (DASS-21): psychometric properties in adults of the province of San Martín - Tapullima Mori, Calixto (2021)
The objective of the study was to analyze the psychometric properties of the DASS-21 Scale in adults from the Province of San Martín, 403 people (34%) men and (66%) women from 18 years old participated, it was a psychometric study and instrumental design applying the survey and the questionnaire as an instrument as a technique, it was obtained as results that the items did not present extreme levels, nor presence of bias at the time of being answered, in the same way the CFA demonstrated consistency in the oblique model of three factors CFI = .936, TLI = .922, RMSEA = .054 and SRMR = .047, in addition the scale is invariant in sex and age CFI (ΔCFI <.015) and RMSEA (ΔRMSEA> .01) and a reliability> .70 In this way, it is shown that the scale has adequate psychometric properties for the study sample.